2020
DOI: 10.16916/aded.774465
|View full text |Cite
|
Sign up to set email alerts
|

Türkçe Öğretmeni Adaylarının Akademik Yazma Becerilerine İlişkin Görüşleri

Abstract: Öz Yükseköğretimin amaçlarından biri bilimsel araştırmalar ve çalışmalar yaparak bilgi üretimi sağlamaktır. Öğrencilerin yükseköğretime başladıkları andan itibaren okudukları kaynakları, yaptıkları ödevleri, verdikleri sınavları kapsayan, belli ölçütleri olan, öğrenilebilir ve geliştirilebilir bir beceri olarak tanımlanabilecek akademik yazma bilgi üretiminin temelini oluşturmaktadır. Bu çalışmada, Türkçe öğretmeni adaylarının akademik yazma ile ilgili görüş ve deneyimleri hakkında fikir sahibi olmak amaçlanmı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…When the academic texts written before the implementation are examined, it is seen that the students had various deficiencies in writing academic texts. As a matter of fact, in other studies conducted with Turkish teacher candidates, the findings have also revealed that some students did not understand the language used in scientific texts (Yücelşen and ve Edizer, 2020), made mistakes in writing planning, had difficulty in finding the main idea and supporting idea (Arıcı, 2008), and could not provide logical integrity in the text (Göçer, 2010). Moreover, most of the Turkish teacher candidates who participated in the research conducted by Yücelşen and ve Edizer (2020) emphasized that they had difficulties in this regard because they had not practiced academic writing before.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When the academic texts written before the implementation are examined, it is seen that the students had various deficiencies in writing academic texts. As a matter of fact, in other studies conducted with Turkish teacher candidates, the findings have also revealed that some students did not understand the language used in scientific texts (Yücelşen and ve Edizer, 2020), made mistakes in writing planning, had difficulty in finding the main idea and supporting idea (Arıcı, 2008), and could not provide logical integrity in the text (Göçer, 2010). Moreover, most of the Turkish teacher candidates who participated in the research conducted by Yücelşen and ve Edizer (2020) emphasized that they had difficulties in this regard because they had not practiced academic writing before.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…The aforementioned student statements can also be found in the quantitative research results, and it is seen that the least developed topic is "citation. " Similarly, in another study, it was revealed that more than half of the Turkish language teaching students participating in the research conducted by Yücelşen and ve Edizer (2020) do not know that they should indicate the sources they use, and that there is no student who knows the correct way of citing sources. In addition, the fact that Google Scholar was preferred among the platforms used by the students in the literature review process and that ULAKBİM, Elsevier or ERIC platforms were not preferred can be seen as supporting data for similar study groups.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan alan yazın incelemeleri doğrultusunda ortaokul öğrencilerinin ana dilde yaşadıkları yazma kaygısı (İşeri ve Ünal, 2012;Arslan, 2018;Tayşi ve Taşkın, 2018;Ateş ve Akaydın, 2015;Öztürk, 2012;Yaman, 2014), üniversite öğrencilerinin, öğretmen adaylarının yaşadıkları yazma kaygısı (Kalaycı ve Erdoğan, 2017;Yücelşen ve Edizer, 2020;Demirel, 2019;İşeri ve Ünal, 2012;Tiryaki, 2011) ve yabancı dil olarak Türkçenin öğretiminde yaşanan yazma kaygıları (İşcan, 2015;Karateke Bayat ve Gün, 2018;Şen ve Boylu, 2017;Azizoğlu ve Tolaman, 2019;Seyedi, 2019;Bahşi ve Ateş, 2021) çalışmalarının mevcut olduğu görülmüştür. Ancak yüksek lisans eğitimi alan öğrenciler üzerinde böyle bir çalışmaya rastlanılmamış olması bu çalışmanın özgünlüğü açısından önemli görülmektedir.…”
Section: Sonuç Ve Tartışmaunclassified
“…Yazma becerisi diğer dil becerileri ile doğru orantılıdır. Yücelşen (2021), okuma alışkanlığı kazanamamış bireylerin yazma becerilerinde sorun yaşamasının kaçınılmaz olduğuna dikkat çeker. Ayrıca metin oluşturma becerisinin kazanılmasında sözcük dağarcığı, dil duyarlılığı ve düşünme becerisinin de önemi büyüktür.…”
Section: Introductionunclassified